Rapid Detection of Highly Pathogenic Avian Influenza H5N1 Virus by TaqMan Reverse Transcriptase-Polymerase Chain Reaction - Shankar, B.P.; Gowda, R.N.S.; Pattnaik, B.; Prabhu, B.H. Manjunath; Patil, S.S.; Pradhan, H.K. (International Journal of Poultry Science, 2009)
Highly pathogenic Avian Influenza (AI) H5N1 viruses have been spreading from Asia since late 2003. Early detection and classification are paramount for control of the disease because these viruses are lethal to birds and have caused fatalities in humans. Here we describe a TaqMan Reverse Transcriptase-Polymerase Chain Reaction Assay for rapid detection of Avian Influenza virus and for H5 subtyping by targeting HA gene of AI viruses. The assay was highly sensitive than RT-PCR and virus isolation in chick embryos. In the present study all samples (field samples) which are positive for HI and RT-PCR were tested by using TaqMan Reverse Transcriptase-Polymerase Chain Reaction Assay for reconfirmation. AI viruses (H5N1) were detected from nine samples which are received from Maharashtra during Avian influenza outbreak in India in 2006. Real-Time PCR assays was also conducted for detection of viral genome in different organs of experimental infected chickens revealed presence of the virus in all organs with high virus concentration in brain, heart, intestine and cloaca. This test allows definitive confirmation of an AI virus as H5 within hours, which is crucial for rapid implementation of control measures in the event of an outbreak.